Synthesis of 2-(alkylamino)-1-phenylethane-1-thiosulfuric acids, potential schistosomicides - Moreira,Liliani Salum Alves (2000)
The total synthesis of seven here-to-fore unreported aromatic aminoalkanethiosulfuric acids, their physical properties and those of the aminoalcohol and bromoalkanamine intermediates are reported. All structures were established by including ¹H and 13C NMR, IR and MS spectroscopy and elemental analysis.